Structurall features of the pancreas in patients with type 1 diabetes mellitus - M. R. Ragimov; T. V. Nikonova; D. M. Babaeva; V. P. Vladimirova; M. V. Shestakova (Сахарный диабет, 2022)
BACKGROUND: Observation of changes in the volume and size of the pancreas has a long history, however, the results of studies are still not unambiguous, the specific causes of changes in pancreatic volume, as well as their consequences, are not clear. According to some data, the decrease of pancreas volume in life expectancy is 35–45% in the population of patients with a long history of type 1 diabetes, and about 20–25% during the first year of the disease. Interestingly, in T1D in 20–45% of cases, the development of exocrine pancreatic insufficiency is noted, one of the manifestations of which is pancreatic atrophy, leading to a decrease in life expectancy.AIM: Assess the volume and size of the pancreas, as well as factors that can influence on their changes.MATERIALS AND METHODS: The study included 78 patients with type 1 diabetes mellitus, the control group consisted of 23 people without previously identified disorders of carbohydrate metabolism, comparable in age and anthropometric parameters with the study group. RESULTS: The volume and dimensions of the pancreas were statistically significantly less in patients with T1D than in the control group. In addition, the influence of the duration of T1D and the age of onset of the disease on these indicators has been proven.CONCLUSION: The volume and size of the pancreas in patients with T1D is less than in healthy individuals. It is necessary to  study the effect of these changes on the function of the pancreas.